Tumor-Associated Macrophages in Vestibular Schwannoma and Relationship to Hearing. Issue 4 (November 2021) - Nisenbaum, Eric; Misztal, Carly; Szczupak, Mikhaylo; Thielhelm, Torin; Peña, Stefanie; Mei, Christine; Goncalves, Stefania; Bracho, Olena; Ma, Ruixuan; Ivan, Michael E.; Morcos, Jacques; Telischi, Fred; et al.
Objective: (1) Characterize the distribution of M1 and M2 macrophages in vestibular schwannomas by hearing status. (2) Develop assays to assess monocyte migration and macrophage polarization in cocultures with vestibular schwannoma cells. Study Design: Basic and translational science. Setting: Tertiary care center. Methods: A retrospective chart review of 30 patients with vestibular schwannoma (VS) was performed. Patients were stratified into serviceable and unserviceable hearing groups. Immunohistochemistry for CD80 + M1 and CD163 + M2 macrophages was conducted. Primary VS cultures (n = 4) were developed and cocultured with monocytes. Immunohistochemistry for macrophage markers was performed to assess monocyte migration and macrophage polarization. Results: Although tumors associated with unserviceable hearing had higher levels of CD80 and CD163 than those with serviceable hearing, the relationship was only significant with CD163 ( P = .0161). However, CD163 level did not remain a significant predictor variable associated with unserviceable hearing on multivariate analysis when adjusted for other variables. In vitro assays show that VS cells induced monocyte migration and polarization toward CD80 + M1 or CD163 + M2 macrophage phenotypes, with qualitative differences in CD163 + macrophage morphologies between serviceable and unserviceable hearing groups. Conclusion: Vestibular schwannomas express varying degrees of CD80 + M1 and CD163 + M2 macrophages. We present evidence that higher expression of CD163 + may contribute to poorer hearing outcomes in patients with VS. We also describe in vitro assays in a proof-of-concept investigation that VS cells can initiate monocyte migration and macrophage polarization. Future investigations are warranted to explore the relationships between tumor, macrophages, secreted cytokines, and hearing outcomes in patients with VS.